Partitioning Apomixis Components to Understand and Utilize Gametophytic Apomixis - Kaushal, Pankaj; Dwivedi, Krishna K.; Radhakrishna, Auji; Srivastava, Manoj K.; Kumar, Vinay; Roy, Ajoy Kumar; Malaviya, Devendra R. (Frontiers in Plant Science, 2019)
Apomixis is a method of reproduction to generate clonal seeds, and offer tremendous potential in agriculture. The process of apomictic seed development is complex and comprises of three distinct components, viz., apomeiosis (leading to formation of unreduced egg cell), parthenogenesis (development of embryo without fertilization) and functional endosperm development. Recently, in many crops, these three components are reported to be uncoupled leading to their partitioning. This review provides an insight into recent status of our understanding of partitioning apomixis components in gametophytic apomictic crops, along-with possible consequences leading to diversity in seed formation pathways, resources to understand apomixis, inheritance and identification of candidate gene(s) for partitioned components as well as contribution towards creation of variability and the process of speciation. Modifications in cytogenetic status as well as endosperm imprinting effects arising due to partitioning effects are also discussed. Further, potential of Panicum maximum, an aposporous crop, has been discussed as a model crop to study partitioning principle and effects.